Gastric mucormycosis in an immunocompetent patient with fatal outcome (BIRDEM Medical Journal, 2021)
Mucormycosis is being reported as a serious fungal infection with grave outcomes among patients recovering from corona virus disease 2019 (COVID-19). This condition is a new challenge for the physicians in this pandemic situation. Mucormycosis predominantly occurs among patients with immunosuppression but immunocompetent patients are not immune. Here, we report a case of gastric mucormycosis occurring in an immunocompetent patient during the pre-COVID era. Patient presented with fever and upper gastro-intestinal bleeding. Diagnostic work-up confirmed gastric mucormycosis. His response to medical management was unsatisfactory and he died while awaiting a gastric resection.BIRDEM Med J 2021; 11(3): 223-226